OCORRÊNCIA DE ANTICORPOS ANTI-NEOSPORA CANINUM EM FÊMEAS BUBALINAS DA REGIÃO OESTE DO ESTADO DE SÃO PAULO - Negrão, C.b. [UNESP]; Aguiar, D.m.; Orlandelli, R.c.; Sartor, I.f. [UNESP] (Instituto Biológico, 2021)
Serum samples from 404 females water buffaloes (Bubalus bubalis) were tested to verify the occurrence of anti-Neospora caninum antibodies in 5 counties in the west region of São Paulo State, Brazil. The technique used was indirect fluorescence antibody test (IFAT), with initial dilutions of 1:100. AntiNeospora caninum antibodies were observed in 38.1% (154/404) of the samples, and antibody titers ranged from 100 to 12,800. The frequency observed among the counties ranged from 16.2% to 61.4% (P < 0.05). Animals from Lucelia County older than 5 years of age presented higher antibody frequencies (P < 0.05). These results are a warning signal for N. caninum infection in water buffaloes in the west region of São Paulo State.

Foram testadas 404 amostras de soro de fêmeas bubalinas (Bubalus bubalis) para se verificar a ocorrência de anticorpos anti-Neospora caninum em rebanhos oriundos de cinco municípios da região oeste do Estado de São Paulo. Empregou-se a técnica da Reação de Imunofluorescência Indireta (RIFI), na diluição inicial de 1:100. Foram observados anticorpos antiNeospora caninum em 38,1% (154/404) dos soros testados, com títulos de anticorpos variando de 100 a 12.800. A frequência de animais sororeagentes observada entre os municípios variaram de 16,2 a 61,4% (P < 0,05). A faixa etária dos animais soropositivos apresentou diferença significativa no Município de Lucélia, onde as vacas com idade superior a 5 anos apresentaram maior frequência de infecção (P < 0,05). Esses resultados alertam para a presença da infecção em bubalinos da região Oeste do Estado de São Paulo.
OCCURRENCE OF ANTI-NEOSPORA CANINUM ANTIBODIES IN FEMALE WATER BUFFALOES (BUBALUS BUBALIS) IN THE WEST REGION OF SÃO PAULO STATE, BRAZIL
Keywords: Occurrence; water buffaloes; immune fluorescence; Neospora caninum; ocorrência; búfalos; imunofluorescência